Association between the exposure to brominated flame retardants and psoriasis risk among U.S. adults: A population-based study - Jingbo Zhang; Xiangyun Shi; Genlong Bai; Jin Chen; Yidian Fu; Aijun Chen (Ecotoxicology and Environmental Safety)
Psoriasis risk can be affected by exposure to mixtures of environmental chemicals; however, the effect of brominated flame retardants (BFRs) exposure on self-reported psoriasis has not been assessed. Herein, we evaluated the association between the exposure to BFRs compounds of 6 chemicals with risk of psoriasis. Based on data from the National Health and Nutrition Examination Survey (NHANES) 2003–2006 and 2009–2014, this analysis was conducted among 6340 adults. Multivariable logistic regression, restricted cubic splines (RCS), weighted quantile sum (WQS) regression, quantile-based g computation (Qgcomp) regression, and Bayesian kernel machine regression (BKMR) models were performed to estimate the associations. Our results indicated that co-exposure to BFRs was associated with increased risk of psoriasis. Notably, PBB153 emerged as a significant factor contributing to the risk of psoriasis, and showed a non-linear relationship between the concentration of serum PBB153 and the prevalence of psoriasis. Moreover, the association between PBB153 and psoriasis risk remained stable across all subgroup analyses, including those stratified by gender. Our study presents robust evidence connecting BFRs exposure to the prevalence of psoriasis, emphasizing the necessity for continued research and policy interventions to address this environmental health issue. Because BFRs are extensively used and detected in various environmental sources and living organisms, future investigations should further elucidate the mechanisms underlying the observed associations between BFRs exposure and psoriasis risk.